Signaling via the Interleukin-10 Receptor Attenuates Cardiac Hypertrophy in Mice During Pressure Overload, but not Isoproterenol Infusion - Stafford, Nicholas; Assrafally, Farryah; Prehar, Sukhpal; Zi, Min; De Morais, Ana M.; Maqsood, Arfa; Cartwright, Elizabeth J.; Mueller, Werner; Oceandy, Delvac (Frontiers in Pharmacology, 2020)
Inflammation plays a key role during cardiac hypertrophy and the development of heart failure. Interleukin-10 (IL-10) is a major anti-inflammatory cytokine that is expressed in the heart and may play a crucial role in cardiac remodelling. Based on the evidence that IL-10 potentially reduces pathological hypertrophy, it was hypothesised that signalling via the IL-10 receptor (IL10R) in the heart produces a protective role in reducing cardiac hypertrophy. The aim of this study was to investigate the effects of the ablation of Il-10-r1 gene during pathological cardiac hypertrophy in mice. We found that IL-10R1 gene silencing in cultured cardiomyocytes diminished the anti-hypertrophic effect of Il-10 in TNF-alpha induced hypertrophy model. We then analysed mice with deficient in the Il-10-r1 gene (IL-10R1-/- mice) and subjected them to transverse aortic constriction (TAC) or isoproterenol infusion to induce pathological hypertrophy. In response to TAC for 2 weeks, IL-10R1-/- mice displayed a significant increase in the hypertrophic response as indicated by heart weight/body weight ratio, which was accompanied by significant increases in cardiomyocyte surface area and interstitial fibrosis. In contrast, there was no different in hypertrophic response to isoproterenol infusion (10 days) between the knockout and control groups. Analysis of cardiac function using echocardiography and invasive haemodynamic studies did not show any difference between the WT and IL-10R1-/- groups, most likely due to the short term nature of the models. In conclusion, our data shows that signalling via the IL-10 receptor may produce protective effects against pressure overload-induced hypertrophy but not against β-adrenergic stimuli in the heart. Our data supports previous evidence that signalling modulated by IL-10 and its receptor may become a potential target to control pathological cardiac hypertrophy.